Multidimensional evaluation of decent work in the Puno Region: 2013–2017 - Tudela-Mamani, Juan Walter (2020)
Like many regions of Peru, the Puno region is an area where there are no adequate working conditions, and this is reflected in indicators of occupation, unemployment and underemployment, all derived from non-compliance with labor rights. The general objective of the research is to prepare a multidimensional index of decent work in the Puno region, specifically, the aim is to assess the conditions of job vulnerability and estimate the factors that explain the presence of decent work. We worked with the ENAHO survey, taking as analysis only the occupied PEA. The multidimensional index was developed using principal component analysis. For the estimation of the determining factors that explain the presence of decent work, the ordered multinomial logit model was used. The multidimensional decent work index for the Puno region in the period 2013-2017 resulted in 0,33 - vulnerable work category. The most likely to have a decent job are workers belonging to the extractive branch. Furthermore, unlike other sectors, public sector workers are more likely to have decent work, which indicates that this sector has better working conditions.